Marital Satisfaction in Terms of Communication, Conflict Resolution, Sexual Intimacy, and Financial Relations among Working and Non-Working Wives - Renanita, Theda; Setiawan, Jenny Lukito (Makara Human Behavior Studies in Asia, 2018)
One of the signs of a successful marriage is marital satisfaction of both husbands and wives. However, in the current era, addressing the role of wives who work outside the house hold has been a challenge for some married couples. The aim of this study is to examine the influences of communication, conflict resolution, sexual intimacy, and financial relations on the marital satisfaction of working and non-working wives. The study was conducted on a total of 144 subjects consisting of 90 full-time working wives and 54 non-working wives. Data collection was conducted through questionnaires. Results of linear regression analysis showed a difference in the factors affecting marital satisfaction in working and non-working wives. Marital satisfaction in working wives was influenced by communication, sexual intimacy, and financial relations; while marital satisfaction in non-working wives was influenced by communication and financial relations.